Varves of the Dead Sea sedimentary record. (1st July 2019) - Ben Dor, Yoav; Neugebauer, Ina; Enzel, Yehouda; Schwab, Markus J.; Tjallingii, Rik; Erel, Yigal; Brauer, Achim
Abstract: The sedimentary record of the Dead Sea provides an exceptional high-resolution archive of past climate changes in the drought-sensitive eastern Mediterranean-Levant, a key region for the development of humankind at the boundary of global climate belts. Moreover, it is the only deep hypersaline lake known to have deposited long sequences of finely laminated, annually deposited sediments ( i.e. varves) of varied compositions, including aragonite, gypsum, halite and clastic sediments. Vast efforts have been made over the years to decipher the environmental information stored in these evaporitic-clastic sequences spanning from the Pleistocene Lake Amora to the Holocene Dead Sea. A general characterisation of sediment facies has been derived from exposed sediment sections, as well as from shallow- and deep-water sediment cores. During high lake stands and episodes of positive water budget, mostly during glacial times, alternating aragonite and detritus laminae ('aad' facies) were accumulated, whereas during low lake stands and droughts, prevailing during interglacials, laminated detritus ('ld' facies) and laminated halite ('lh' facies) dominate the sequence. In this paper, we (i) review the three types of laminated sediments of the Dead Sea sedimentary record ('aad', 'ld' and 'lh' facies), (ii) discuss their modes of formation, deposition and accumulation, and their interpretation as varves, and (iii) illustrate how Dead Sea varves are utilized for palaeoclimate reconstructions and for establishing floating chronologies. Graphical abstract: Image 1 Highlights: The Dead Sea is the only deep hypersaline lake with varved sediments. The chronological and paleoclimatic value of Dead Sea varves is demonstrated. The interpretation of alternating aragonite-detritus laminae as varves is evaluated. Lake monitoring confirms the interpretation of laminated halite as varves. Distinguishing between annual and non-annual laminations requires micro-facies analyses.